Biosynthesis of SUMOylated proteins in bacteria using the trypanosoma brucei enzymatic system - Iribarren, Paula Ana (2015)
Post-translational modification with the Small Ubiquitin-like Modifier (SUMO) is conserved in eukaryotic organisms and plays important regulatory roles in proteins affecting diverse cellular processes. In Trypanosoma brucei, member of one of the earliest branches in eukaryotic evolution, SUMO is essential for normal cell cycle progression and is likely to be involved in the epigenetic control of genes crucial for parasite survival, such as those encoding the variant surface glycoproteins. Molecular pathways modulated by SUMO have started to be discovered by proteomic studies; however, characterization of functional consequences is limited to a reduced number of targets. Here we present a bacterial strain engineered to produce SUMOylated proteins, by transferring SUMO from T. brucei together with the enzymes essential for its activation and conjugation. Due to the lack of background in E. coli, this system is useful to express and identify SUMOylated proteins directly in cell lysates by immunoblotting, and SUMOylated targets can be eventually purified for biochemical or structural studies. We applied this strategy to describe the ability of TbSUMO to form chains in vitro and to detect SUMOylation of a model substrate, PCNA both from Saccharomyces cerevisiae and from T. brucei. To further validate targets, we applied an in vitro deconjugation assay using the T. brucei SUMO-specific protease capable to revert the pattern of modification. This system represents a valuable tool for target validation, mutant generation and functional studies of SUMOylated proteins in trypanosomatids. Copyright: